Los tisanópteros del grupo genérico Anaphothrips(Thysanoptera: Thripidae), con énfasisen América Central - P. Retana Salazar, Axel (2007)
A taxonomic revision and phylogenetic analysis of the generic group Anaphothrips are presented. Several genera in Central America are closely related to this generic group. Based on the analysis of characters and its possible evolution, the new genus Nakaharathrips has been segregated from Anaphothrips, and the taxonomic status of the subspecies of Aurantothrips has been changed to the species level. The phylo-genetic analysis shows a close relationship between the genera Anaphothrips, Ranjana, Nakaharathrips n.gen., Aurantothrips, Nicolemma n.gen., Ameranathrips, Baileyothrips and Gonzalezya n.gen., where the first lineage is formed by the genera (Ranjana (Aurantothrips+Nicolemma)) and the second lineage contains the genera [(Anaphothrips+Nakaharathrips)(Baileyothrips (Ameranathrips+Gonzalezya)].